PRACTICAL ASPECTS OF LOGISTICS OPTIMIZATION - Rashidov Uchkun (Scholar Express Journals, 2024)
This article examines the practical aspects of logistics optimization, highlighting specific areas within logistics that can be optimized and their primary objectives. Additionally, practical recommendations for effective logistics optimization are presented.
Keywords: logistics; logistics optimization